2014
DOI: 10.1007/s11633-014-0760-2
|View full text |Cite
|
Sign up to set email alerts
|

A Progressive Deployment Strategy for Cooperative Adaptive Cruise Control to Improve Traffic Dynamics

Abstract: Cooperative adaptive cruise control (CACC) vehicles are intelligent vehicles that use vehicular ad hoc networks (VANETs) to share traffic information in real time. Previous studies have shown that CACC could have an impact on increasing highway capacities at high market penetration. Since reaching a high CACC market penetration level is not occurring in the near future, this study presents a progressive deployment approach that demonstrates to have a great potential of reducing traffic congestions at low CACC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…In order to model the behaviour of AVs and CAVs in microsimulation frameworks, various models with vastly different results have been presented on various studies mentioned in the state-of-the-art section [3,[6][7][8][9][10][11][12][13][14][15]. It has been assumed that the AVs and CAVs cruising behaviour can be simulated using models developed to describe ACC and CACC cruising controllers.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…In order to model the behaviour of AVs and CAVs in microsimulation frameworks, various models with vastly different results have been presented on various studies mentioned in the state-of-the-art section [3,[6][7][8][9][10][11][12][13][14][15]. It has been assumed that the AVs and CAVs cruising behaviour can be simulated using models developed to describe ACC and CACC cruising controllers.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…The system resulted in an increased lane capacity of the highway from 2200 to 4000 vphpl at 100% CV MP level. Further, the authors in [33, 34] explored the effect of CV technologies, in the form of CACC, on a multi‐lane freeway. Results showed that CVs positively impacted traffic capacity [33] and traffic flow dynamics [34], especially in high traffic densities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, the authors in [33, 34] explored the effect of CV technologies, in the form of CACC, on a multi‐lane freeway. Results showed that CVs positively impacted traffic capacity [33] and traffic flow dynamics [34], especially in high traffic densities. In general, results showed the ability of V2V communication to improve traffic performance and reduce traffic congestion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al [2] evaluated the mobility and safety impact of CACC using Vissim with an active platooning algorithm. Arnaout and Bowling [3] evaluated three different deployment strategies for CACC with a custom simulation testbed. The benefits of CACC start to show when the market penetration rate (MPR) reaches 40% in the absence of any managed lane strategies.…”
Section: Literature Reviewmentioning
confidence: 99%